Effects of Revised Consultation Room Design on Patient–Physician Communication. (January 2015) - Ajiboye, Folaranmi; Dong, Fanglong; Moore, Justin; Kallail, K. James; Baughman, Allison
Objective: To evaluate the impact of a revised consultation room design on patient–physician interaction in an outpatient setting. Background: The growth of ambulatory medical care makes outpatient facilities the primary point of health care contact for many Americans. However, the outpatient consultation room design remains largely unchanged, despite its increased use and the adoption of technology-mediated information sharing in clinical encounter. Methods: A randomized controlled trial used a postvisit questionnaire to assess six domains of interest (satisfaction with the visit and the consultation room, mutual respect, patient trust in the physician, communication quality, people–room interaction, and interpersonal–room interaction) in two different room designs (a traditional room and an experimental room in which a pedestal table had replaced the examination table). Results: Interpersonal–room interaction was enhanced in the experimental consultation room when compared to the traditional consultation room ( p = .0038). Participants in the experimental consultation room had better access to the computer screen, increased provider information sharing, and more time engaging providers in conversation about information on the monitor. Conclusions: Changing the layout of a consultation room has the potential to improve interpersonal communication through better information sharing. Clinicians who are interested in maximizing the benefits of their clinical encounter should consider changing the layout of their consultation room, especially the positioning of the computer screen.